A child's world : infancy through adolescence - Papalia, Diane E. 4 0 16; Olds, Sally Wendkos.;Feldman, Ruth Duskin; 5 (Boston : McGraw-Hill, 1999)
A study of child development, emphasizing the continuity of development from conception through adolescence, and the interrelationships among the physical, cognitive, and psychosocial realms.
Includes bibliographical references (p. 621-668) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Child development.;Child psychology.;Adolescence.;Child development.;Child psychology.;Adolescence.; 20; 2